Pengalaman Memoderasi Pengaruh Tekanan Waktu, Skeptisisme Profesional, Dan Independensi Terhadap Pendeteksian Kecurangan Dalam Audit Investigasi - Naila Fadhilni; Marsellisa Nindito; Ayatulloh Michael Musyaffi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This research was conducted to determine the effect of time pressure, professional skepticism, and auditor independence on fraud detection in investigative audits with experience as a moderating variable. This research uses quantitative research methods, with primary data collected through questionnaires. The sample consisted of 62 Investigative Auditors who worked at the DKI Jakarta Province BPKP Representative. Data analysis was carried out using the Structural Equation Model (SEM) method based on Partial Least Square and processed using the SmartPLS 3.0 program. The research results show that time pressure and independence have no effect on fraud detection, professional skepticism has an effect on fraud detection, and experience moderates the relationship between professional skepticism and fraud detection. However, experience does not moderate time pressure and independence on fraud detection